(untitled) (The Review of Diabetic Studies, 2015)
This article reviews the impact of diabetes and its treatment on vascular function with a focus on the reactivity of epineurial arterioles, blood vessels that provide circulation to the sciatic nerve. Another focus is the relationship between the dysregulation of neurovascular function and diabetic peripheral neuropathy. Diabetic peripheral neuropathy is a debilitating disorder that occurs in more than 50 percent of patients with diabetes. The etiology involves metabolic, vascular, and immunologic pathways besides neurohormonal growth factor deficiency and extracellular matrix remodeling. In the light of this complex etiology, an effective treatment for diabetic peripheral neuropathy has not yet been identified. Current opinion postulates that any effective treatment for diabetic peripheral neuropathy will require a combination of life style and therapeutic interventions. However, a more comprehensive understanding of the factors contributing to neurovascular and neural dysfunction in diabetes is needed before such a treatment strategy can be developed. After reading this review, the reader should have gained insight into the complex regulation of vascular function and blood flow to the sciatic nerve, and the impact of diabetes on numerous elements of vascular reactivity of epineurial arterioles of the sciatic nerve.